Experimental Study of Asphalt Tile Waste as a Substitute for Coarse Aggregate and Fly Ash as a Partial Substitution of Cement in Concrete Mixtures on Compressive Strength - Sumarno, Agung; Firmansyah, Lugawi Lodra (ARRUS Journal of Engineering and Technology, 2022)
The increasing growth of residential construction, as well as construction waste is also increasing, including tile roof waste. So this study will process the tile fragments or waste to mix concrete as a substitute for coarse aggregate and fly ash as a partial substitution of cement for compressive strength. The purpose of this study was to determine the effect on slump, water absorption, density, and compressive strength of concrete. The method used in this research is experimental by conducting a trial mix which is carried out at the Concrete Laboratory of DSP - PT. Duta Sarana Prakarsa. From the research results of asphalt tile waste and fly ash substitution, there is a slump level of 6 cm - 8 cm, normal concrete has a slump value of 7 cm. The highest slump value is found on 20% asphalt tile, which is 8 cm from normal concrete. The biggest slump decrease occurred in 10% asphalt tile and 10% fly ash from normal concrete. At the age of 28 days, it can be seen that normal concrete has a water absorption value of 3.78%. Meanwhile, the water absorption with the highest value is found in 20% asphalt tile, which is 4.93%. The lowest water absorption value occurs in 10% asphalt tile, which is 3.40%. At the percentage of the mixture of 20% asphalt tile waste and 10% fly ash, the density decreased the most by 7.93% from normal concrete. The compressive strength value of normal concrete at the age of 28 days was 389.91 Kg/Cm2. The greatest decrease in compressive strength occurred in a mixture of 20% asphalt tile waste and 10% fly ash, which was 156.51 Kg/Cm2.